Factors affecting lung function among motorcycle taxi drivers in Thonburi district, Bangkok - Prasansri, Alongkot; Chompook, Pornthip (Science, Engineering and Health Studies, 2025)
Motorcycle taxi drivers are another occupational group whose work inevitably exposes them to air pollution. This exposure places them at a higher risk of respiratory diseases and impaired lung function. This cross-sectional analytical study aimed to determine the prevalence of respiratory diseases and lung function impairments, along with their associated factors. A total of 208 participants were interviewed, and their lung function was tested using spirometry. The lung function parameters evaluated included forced vital capacity (FVC), forced expiratory Volume in the first second (FEV1), and forced vital capacity ratio (FEV1/FVC). The prevalence of abnormal lung function was found to be 53.85%. Moreover, the results also showed the prevalence of respiratory symptoms: coughing, phlegm, difficulty breathing, and wheezing. Factors associated with impaired lung function were identified, including being in the age 40–49-year age group, which significantly increase the risk of impaired lung function. Conversely, being overweight was found to reduce the risk. The study suggests that a surveillance system for monitoring lung function among motorcycle taxi drivers can focus on drivers aged 40 years and above, those who are underweight and at risk of impaired lung function, and individuals with respiratory symptoms, particularly coughing, as it is a key factor associated with lung function impairment.